2022
DOI: 10.1111/jfpp.16501
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound to extend the shelf life of shalgam juice: Changes in various physicochemical, nutritional, and microbiological properties

Abstract: Shalgam juice is a traditional lactic acid fermented beverage, which has intense red color and sourish taste. This study aimed to determine various physicochemical and microbiological changes in shalgam juice after ultrasound application to extend the shelf life of the juice. Ultrasound was applied to the samples at different amplitudes, temperatures, and times in combination. Analyses were performed on the samples at five different stages throughout the storage. The lactic acid amount, lactic acid bacteria co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…1(C)). Admittedly, our b* values were lower than that of some shalgam juice studies 44,45 . However, the b* values determined in the study of Tanguler et al ., 34 who used similar production methods to this study, were compatible with our outcome.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…1(C)). Admittedly, our b* values were lower than that of some shalgam juice studies 44,45 . However, the b* values determined in the study of Tanguler et al ., 34 who used similar production methods to this study, were compatible with our outcome.…”
Section: Resultssupporting
confidence: 84%
“…Admittedly, our b* values were lower than that of some shalgam juice studies. 44,45 However, the b* values determined in the study of Tanguler et al, 34 who used similar production methods to this study, were compatible with our outcome. Therefore, the differences detected in the b* values were probably due to differences in production methods.…”
Section: Total Dry Matter Content and Color Attributessupporting
confidence: 90%
See 2 more Smart Citations
“…4 ). Ulucan et al (2022) documented a notable rise in TAC and shelf life following 50 °C and 15-minute ultrasound treatment of turnip juice [49] . Bayati et al (2021) showed a 5.45 % decrease in TAC in their ultrasound treatment of pomegranate juice compared to the control [50] .…”
Section: Resultsmentioning
confidence: 99%